Headache as anUnusual Presentation of Ischemic Heart Disease: A Case Report - Chowdhury, Abdul Wadud; Sarker, Sudhakar; Ali, Mohammad; Hasan, Pratyay; Rahman, Sazedur; Islam, Md Rafiqul; Mohammad, Quazi Deen (Journal of National Institute of Neurosciences Bangladesh, 2019)
The clinical features of coronary artery disease vary, and patients may present with symptoms other than chest pain, such as headache. Rarely, the headache may be theonly presenting feature without any chest discomfort, and may be confused with migraine. Failure to distinguish such headache, caused by CAD, from migraine may result in wrong treatment with disastrous fate. Elderly patient with the presence of cardiovascular risk factors having recent onset exertional headache should be evaluated for the presence of cardiac cephalgia.We intend to report a 60-year-old hypertensive, diabetic patient with a 6-months history of episodic exertional headaches, who turned out to be a case of headache angina (cardiac cephalgia). Journal of National Institute of Neurosciences Bangladesh, 2019;5(1): 81-86